IMPLEMENTASI PENGEMBANGAN KEBERAGAMAAN PESERTA DIDIK DI SEKOLAH: Studi Kasus SMA Negeri 1 Simpenan - Anhar Munandar; Encep Solihutaufa (STAI Pelabuhan Ratu, 2021)
The purpose of writing this paper is to describe the implementation of the development of student diversity in SMA Negeri 1 Simpenan. The results of the observations show that the implementation of the religious development of students at SMA Negeri 1 Simpenan has been well actualized and programmed, both carried out by the school as a complete educational institution with policies related to the development of religion in schools and community activities carried out by Rohis (Spiritual of Islam) as one of the extracurricular special schools that overshadow other religious activities. This success can be achieved because of the efforts of the principal and the support of the entire school community by showing their respective commitments that are interrelated and mutually supportive.